Memory bias for social hierarchical information is modulated by perceived social rank. Issue 5 (28th May 2022) - Griffiths, Kirsty; Stretton, Jason; Dalgleish, Tim
ABSTRACT: Hierarchies pervade human society, characterising its members along diverse dimensions ranging from their abilities or skills in a particular domain to their economic status or physical stature. One intriguing aspect of the centrality of hierarchies, relative to egalitarian constructs, is that hierarchically-organised social information appears to be remembered more easily than non-hierarchically-organised information. However, it is not yet clear how one's social rank within a hierarchy influences processing. In a pre-registered study with 66 healthy participants, we examined memory recall for hierarchical information when participants themselves were positioned higher in the hierarchy versus lower in the hierarchy, both relative to an egalitarian control condition. The results replicate previous work showing that hierarchical information is memorised faster relative to the egalitarian control. Importantly, this effect was modulated by the participant's position within the hierarchy, with higher positioned participants memorising information faster than lower-positioned participants. This study provides new evidence showing biases in memory will favour hierarchical information if modulated by perceptions of one's own social rank.